Patient and Public Involvement of young people with a chronic condition in projects in health and social care: A scoping review - Femke vanSchelven; Hennie Boeije; Veerle Mariën; Jany Rademakers (Wiley, 2020)
Abstract Background The involvement of young people with a chronic condition in research and implementation projects in health and social care receives growing attention. Yet, there is a lack of conceptual clarity of this so‐called 'Patient and Public Involvement' (PPI) and methods to systematically evaluate it are absent. This scoping review aimed to gain insight into developments in the existing literature on PPI of young people with a chronic condition by mapping reported definitions, goals, activities, experiences and impact. Methods We conducted searches in Cinahl, Embase, PsycINFO, PubMed and Scopus. Included articles described involvement of young people with a chronic condition in research and implementation projects, contained empirical data, were written in English and were published after 1990. Two researchers independently carried out the data extraction. Results Twenty‐three studies out of 4993 initial hits met the inclusion criteria. We found great variation in definitions and operationalizations of PPI. Reflections of authors on the process of PPI and its impact were similar and did not change over the years. Discussion and conclusion Limited progress in the evidence base of the impact of PPI with young people with a chronic condition was found. Over the years, studies continue to report similar experiences and challenges. In order to move forward, we suggest future research to make connections to existing work instead, to include thorough descriptions of what is understood by PPI and how this is translated into activities, and to use systematic and objective, but also flexible, methods to measure its impact.